Cardiovascular Surgery Patients: Intensive Care Experiences and Associated Factors - Özlem Aslan, RN, PhD; Betül Tosun, RN, PhD (Elsevier, 2015)
Purpose: The purpose of this study was to determine the intensive care unit (ICU) experiences of cardiovascular surgery (CS) patients and to define the associations between their ICU experiences and related factors. Methods: The study used a descriptive design. In total, 106 CS patients were interviewed at least 24 hours after discharge from an ICU in an educational research hospital in Ankara, Turkey between January and July 2012. Data were collected using the Intensive Care Experience Scale (ICES), a sociodemographic and clinical characteristics data form and two open-ended questions inquiring about smells and light. Statistical analyses were conducted using SPSS 15.0. Results: The patients were moderately aware of their ICU environments, partly recalled their ICU experiences, highly recollected frightening experiences, and expressed good satisfaction with care. Age, education, marital status, and pain were associated with ICU experiences. Patients who sensed smell had higher scores of frightening experiences than those who did not. Patients who were annoyed with excessive light reported less satisfaction with care than those who were not. Conclusions: The results suggest that measuring the patients' characteristics and environmental factors may be beneficial for healthcare teams to improve the recovery of CS patients in the ICU.